The Dimensions of Sufi Healing in Traditional Medication of the Islamic-Banjar Community - Muhammad Zainal Abidin; Ridhatullah Assya'bani; Arni Arni; Mulyani Mulyani (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
Sufi healing has become an exciting topic to discuss amid the COVID-19 outbreak. Various alternative health treatments remain a concern from a medical and non-medical perspective. One kind of Sufi healing originating from the Banjar community in South Kalimantan is the practice of Batatamba. This study examines the forms, methods and sources of Sufi healing practice that live and develop in South Kalimantan. The method used in this study is qualitative. The data were collected from field research. It employs an anthropological approach which looks at the Sufi side of healing in the practice of Batatamba.Contribution: This study gives a new insight into Sufi healing that developed in South Kalimantan that combines the Sufistic tradition with local wisdom and the legitimacy of mystics in knowledge transfer (epistemology). The mystical legitimacy has made practitioners of traditional medication in this area, commonly known as Pananamba, have a sacred element and are committed to a humane mission to help others.